Development of an ergonomics risk assessment tool for repetitive task assessment (RTRA). - Ruennusan, Metta; Chaikittiporn, Chalermchai; Taptagaporn, Sasitorn; Boonshuyar, Chaweewon (Work, 2023)
BACKGROUND: Most ergonomics assessment tools for repetitive task have been used in industries which are mainly focused on assessing the biomechanical risk factors that affect musculoskeletal disorders (MSDs) rather than the psychosocial and work environment risk factors. OBJECTIVE: To develop a tool for Repetitive Task Risk Assessment (RTRA) and Rapid Upper Limb Assessment (RULA) that can identify biomechanical, physical stress and psychosocial risk factors, prioritize risk reduction action and systematic record keeping. METHODS: The study consisted of 2 phases; tool development and evaluation of the contents of risk factors by 7 ergonomic experts and intra-rater and inter-rater reliability and validity tests of the tool by 1 researcher and 9 Thai practitioners to assess 30 repetitive tasks. RESULTS: RULA was modified by adding more biomechanical risk, combining psychosocial and work environment risk factors lead to MSD become the first prototype of RTRA. The Item-Objective Congruence Index (IOC) validated 20 items on usability of each step of the RTRA ranged between 0.64 and 0.93. The examination of the overall intra-rater reliability was 0.932 (95% CI: 0.862–0.967) and the overall inter-rater was 0.956 (95% CI: 0.909–0.978). CONCLUSION: The tool has high test-retest reliability. There is a suggestion for researchers to understand more on the identification of multiple risk factors in one assessment tool and consider a risk-level rating and scoring for prioritizing risk reduction.